Environmental Assessment in Marine Areas Beyond National Jurisdiction: Practice and Prospects. (2017) - Warner, Robin
Abstract : Knowledge of the threats posed to the oceans by human activity has expanded beyond marine pollution to encompass recognition of the risks posed to vulnerable marine ecosystems (VMEs) by overfishing, destructive fisheries practices, and invasive exploitation of living and nonliving marine resources. However, with the still-developing state of marine scientific research, the majority of activities at sea continue to occur with limited knowledge of their impacts on the marine environment. In this climate of uncertainty, environmental assessment assumes heightened importance. While governance structures will generally exist to facilitate environmental assessment in marine areas within national jurisdiction, these structures are still developing for marine areas beyond national jurisdiction (ABNJ).